Effects of late aerobic exercise on cardiac remodeling of rats with small-sized myocardial infarction - Souza, Lidiane M. [UNESP]; Okoshi, Marina P. [UNESP]; Gomes, Mariana J. [UNESP]; Gatto, Mariana [UNESP]; Rodrigues, Eder A. [UNESP]; Pontes, Thierres H. D. [UNESP]; Damatto, Felipe C. [UNESP]; Oliveira, Leiliane R. S. [UNESP]; Borim, Patrícia Aparecida [UNESP]; Lima, Aline R. R. [UNESP]; Zornoff, Leonardo A. M. [UNESP]; Okoshi, Katashi [UNESP]; et al. (Sociedade Brasileira de Cardiologia, 2021)
Background: Physical exercise has been considered an important non-pharmacological therapy for the prevention and treatment of cardiovascular diseases. However, its effects on minor cardiac remodeling are not clear. Objective: To evaluate the influence of aerobic exercise on the functional capacity, cardiac structure, left ventricular (LV) function, and gene expression of NADPH oxidase subunits in rats with small-sized myocardial infarction (MI). Methods: Three months after MI induction, Wistar rats were divided into three groups: Sham; sedentary MI (MI-SED); and aerobic exercised MI (MI-AE). The rats exercised on a treadmill three times a week for 12 weeks. An echocardiogram was performed before and after training. The infarction size was evaluated by histology, and gene expression was assessed by RT-PCR. The significance level for statistical analysis was set at 5%. Results: Rats with MI lower than 30% of the LV total area were included in the study. Functional capacity was higher in MI-AE than in Sham and MI-SED rats. The infarction size did not differ between groups. Infarcted rats had increased LV diastolic and systolic diameter, left atrial diameter, and LV mass, with systolic dysfunction. Relative wall thickness was lower in MI-SED than in the MI-AE and Sham groups. Gene expression of the NADPH oxidase subunits NOX2, NOX4, p22phox, and p47phox did not differ between groups. Conclusion: Small-sized MI changes cardiac structure and LV systolic function. Late aerobic exercise is able to improve functional capacity and cardiac remodeling by preserving the left ventricular geometry. NADPH oxidase subunits gene expression is not involved in cardiac remodeling or modulated by aerobic exercise in rats with small-sized MI.
Efeitos do exercício aeróbico tardio na remodelação cardíaca de ratos com infarto do miocárdio pequeno
Keywords: Echocardiography/methods; Exercise, Physical Exercise; Myocardial Infarction; NADPH Oxidase; Rats; Ventricular Dysfunction; Ventricular Remodeling